(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The paper presents the results of determining the granulometric composition of coal from the Uzgen deposit (Changent) by dry sieve analysis. The theoretical foundations of granulometric analysis, methods of sampling and processing of experimental data are considered. Quantitative characteristics of the particle size distribution are obtained and a curve of the granulometric composition is constructed. It was found that small fractions (0.4–0.063 microns) account for up to 70% of the test sample, which determines their prospects for obtaining high-purity coal used in technological studies of electrical conductivity.